2012
DOI: 10.1029/2012ja017868
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric plasma caves under the equatorial ionization anomaly

Abstract: .[1] This paper reports the existence of plasma caves, minima in the electron density located at 5-10 to the magnetic equator, in the bottomside ionosphere based on electron densities simulations from the International Reference Ionosphere (IRI-2007) and clear evidences given by plasma density and drift measurements of the Dynamic Explorer 2 (DE 2) satellite during [1981][1982][1983]. The IRI simulations suggest plasma caves as daytime features (08:00-19:00 LT; length of 18,158 km in the longitudinal direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…[] and Lee et al . [], the depletion belt in the longitude‐latitude map and the two cave‐shaped depletions in the altitude‐latitude map are features of the plasma cave. The plasma caves structure is well developed around 14:01 LT with around 15° width away from the magnetic equator and disappears around 18:00 LT (not shown).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…[] and Lee et al . [], the depletion belt in the longitude‐latitude map and the two cave‐shaped depletions in the altitude‐latitude map are features of the plasma cave. The plasma caves structure is well developed around 14:01 LT with around 15° width away from the magnetic equator and disappears around 18:00 LT (not shown).…”
Section: Resultsmentioning
confidence: 98%
“…Lee et al . [] used satellite in situ observations from Dynamics Explorer 2 (DE‐2) as well as outputs from the empirical International Reference Atmosphere 2007 model and confirmed the existence of plasma caves. They found that the caves are most likely to occur at ~11 LT and 14–17 LT around 0°E–120°E longitudes during the equinoxes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…While theoretical models still struggle to include this phenomenon in their modeling framework, IRI already includes a smoothed version of this phenomenon (McNamara et al, 2010); a smoothing effect is to be expected since IRI is based on monthly averages. Other examples are the midlatitude evening anomaly (Weddell Sea anomaly) observed by the Super Dual Auroral Radar Network (SuperDARN) radars that is well captured by IRI (de Larquier et al, 2011) and the occurrence of ionospheric plasma caves under the Equatorial Ionization Anomaly (EIA) (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…It not only predicts the growth of the X-and O-mode waves but is also an efficient mechanism for direct amplification of waves. This mechanism have also been applied to the generation of Z-and whistler-mode waves, in which these waves can, in turn, further accelerate electrons from a few hundreds of keV to MeV (Lee et al 2012a(Lee et al , 2013a.…”
Section: Solar-solar Wind-magnetospherementioning
confidence: 99%